2012
DOI: 10.1098/rstb.2011.0228
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of miRNA-dependent regulation in root symbiosis

Abstract: The development of root systems may be strongly affected by the symbiotic interactions that plants establish with soil organisms. Legumes are able to develop symbiotic relationships with both rhizobial bacteria and arbuscular mycorrhizal fungi leading to the formation of nitrogen-fixing nodules and mycorrhizal arbuscules, respectively. Both of these symbiotic interactions involve complex cellular reprogramming and profound morphological and physiological changes in specific root cells. In addition, the repress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 57 publications
1
39
0
Order By: Relevance
“…] legume partners are to determine how the association arises, how nodule organogenesis and thus nodule number are regulated, and how nitrogen fixation is controlled. Recently, there has been a great deal of interest in understanding the roles of miRNAs during nodulation in legumes Bazin et al, 2012;Bustos-Sanmamed et al, 2013;Turner et al, 2013). Our analysis here identified miR172c-NNC1 as a critical regulatory module of nodulation that targets early nodulin ENOD40 genes and is essential for nodule initiation and nodule organogenesis in soybean.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…] legume partners are to determine how the association arises, how nodule organogenesis and thus nodule number are regulated, and how nitrogen fixation is controlled. Recently, there has been a great deal of interest in understanding the roles of miRNAs during nodulation in legumes Bazin et al, 2012;Bustos-Sanmamed et al, 2013;Turner et al, 2013). Our analysis here identified miR172c-NNC1 as a critical regulatory module of nodulation that targets early nodulin ENOD40 genes and is essential for nodule initiation and nodule organogenesis in soybean.…”
Section: Discussionmentioning
confidence: 72%
“…Deep sequencing studies have identified a number of miRNAs that are upregulated during nodulation, and ecotopic expression has demonstrated that some are involved in early nodule organogenesis. For example, a specific isoform of miR171 represses critical NODULATION SIGNALING PATHWAY2 (NSP2) expression in M. truncatula and L. japonicus (Devers et al, 2011;Bazin et al, 2012;De Luis et al, 2012). In soybean, numerous miRNAs are differentially expressed during nodule organogenesis (Subramanian et al, 2008;Wang et al, 2009;Dong et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent data from legumes suggest that the repression of NBS-LRR genes by specific miRNAs may have evolved to avoid plant defense responses during symbiotic interactions (Bazin et al, 2012). Such a mechanism could potentially explain the high incidence of miRNA-guided siRNA-mediated degradation of NBS-LRR genes observed in Medicago spp.…”
Section: Sirna-mediated Degradation Of Nbs-lrr Genes Varies Widely Bementioning
confidence: 99%
“…Several profiling studies have revealed that miRNAs are involved in rhizobial infection, nodule formation, and nodule functioning (Subramanian et al, 2008;Lelandais-Brière et al, 2009;Wang et al, 2009;Bazin et al, 2012;De Luis et al, 2012;Dong et al, 2013; for review, see Formey et al, 2014). Indeed, functional analyses have demonstrated an altered number of nodules following miRNA overexpression or knockdown (Combier et al, 2006;Li et al, 2010;De Luis et al, 2012;Turner et al, 2013;Yan et al, 2013;Wang et al, 2014).…”
mentioning
confidence: 99%